Sex and reason - Posner, Richard A. (Harvard University Press, 1992)
How much of a say do we have in our own sexuality? More than is commonly assumed, Richard Posner asserts in this intellectually sweeping and compulsively readable account of sexuality and its social control. While acknowledging that sexual drives and orientations are formed in a fundamentally biological matrix, Posner contends that they are also subject to self-interested choice constrained by perceived costs and benefits. With this approach, he explores numerous puzzles presented by sexual history. Why, for instance, are "macho" cultures generally more tolerant of sexual deviance than their otherwise more sexually liberal Anglo-Saxon counterparts? Why were women in Victorian England less free sexually than women a century earlier? Why might the AIDS epidemic have reduced the ratio of illegitimate to legitimate births? Why is marital rape increasingly criminalized? Economics provides Sex and Reason with its unifying perspective, but Posner also draws heavily on biology, law, psychology, anthropology, history, philosophy, sociology, theology, and women's studies. The scope of his analysis is broad, ranging from ancient Greece to modern Sweden, from African tribal societies to the American Catholic priesthood, from Islamic sexual regulation to the sexual jurisprudence of the U.S. Supreme Court, from polygamy and homosexuality to abortion, surrogate motherhood, and pornography. In all these areas, Posner argues, the rational choice approach can illuminate temporal and cultural variance in sexual norms and practices and point the way to enlightened reform. A widely respected judge and legal scholar, Posner seeks to dispel the clouds of ignorance, prejudice, shame, and hypocrisy that befog the public discussion of sex. His effort is especially timely, coming as it does at a juncture when the American legal system is strained to its limits by such phenomena as the AIDS epidemic, the abortion controversy, the homosexual rights movement, battles over the federal funding of erotic art, and growing attention to sexual harassment and abuse. Lucid, informative, eclectic, and nontechnical, Sex and Reason offers a fresh approach to issues that fascinate, perplex, and ultimately shape society in its most private moments and public gestures